AKOMODASI KOMUNIKASI MASYARAKAT ETNIS JAWA TENGAH DENGAN MASYARAKAT PRIBUMI SUKU TALANG MAMAK DIKABUPATEN INDRAGIRI HULU - Sefti Hariyani; Noor Efni Salam (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The culture of each nation consists of large and small elements. The process of intercultural interaction and communication in Indonesia occurs a lot and is influenced by one of the government's programs, namely transmigration. One of them is Talang Perigi Village, Rakit Kulim Sub-District where the indigenous tribes in the village are Talang Mamak Tribe. At first the Talang Mamak tribe was difficult to interact with Javanese tribes who came from transmigration because the Talang Mamak community was a closed society so it was difficult to interact with Javanese tribes. This study aims to determine the strategy of overcrowding, excessive divergence and accommodation, carried out by the Javanese community with the Talang Mamak tribe community in Talang Perigi Village, Rakit Kulim District, Indragiri Hulu Regency. This study uses a qualitative method. The subjects of this study were Javanese and Talang Mamak tribe. A total of 10 people were selected purposively, consisting of 2 community leaders from each tribe or customary leader, then 3 Javanese people, and 3 people with talang mamak. The technique of collecting data is done through observation, interviews, and documentation. The data analysis technique of this study uses the Interacative analysis model Huberman and Miles. The results of this study indicate that the convergence strategy of the Javanese people and the Talang Mamak tribe in Talang Perigi Village is to adopt the language of the interlocutor, make body movements that indicate attraction, adjust the language of the interlocutor, and wear clothing that does not reflect the difference between his interlocutors. The divergence strategy that is carried out is that there is no effort to know and use the language of the interlocutor, do not make gestures that show interest when communicating, use their own culture of speech, and show differences in the social status of ethnic differences when communicating. The cause of excessive accommodation labeling is the existence of errors in using the language of the interlocutor, excessive in telling the experience and knowledge possessed, and excessive in adapting the distance of communication without understanding the physical condition that is owned. Keywords: Accommodation communication, Intercultural Communication, The Middle Java Tribe and Talang Mamak